Grief and art: sites, games and melancholy objects - Kuhn-Botma, Lyrene (University of the Free State, 2020)
In this Grief and Art: Sites, Games and Melancholy Objects Masters’ research project comprising a written dissertation, an exhibition of drawings, digital drawings, pigment ink drawings with printed silkscreen layers and/or embossing, as well as an exhibition catalogue, I explore personal responses and visual iterations in the wake of grief, bereavement and loss. The objective of this study is to investigate current and alternative responses to grief and loss in terms of visual culture and art. In order to visually and artistically expose and elaborate on difficult experiences of grief and loss, I contrast personal responses to grief, to public and/or cultural responses. I investigate the difficult, unique and communicative iterations of contemporary grief on multiple platforms – every day and digital sites – through artworks that are made using traditional as well as contemporary methods. I include experiences of grief relative to personalised sites and places, video game experiences connected to grief and death, as well as contemporary technological devices and other objects associated with personalised grief. These personal experiences are investigated to explore the visual ways in which experiences of loss and trauma have been communicated through the conduits available in technologically-driven societies, and how these new experiences provide novel empathetic experiences of loss to viewers of artworks. Firstly, specific video games and virtual1 sites are investigated as sites where loss and grief can be expressed as contemporary, personal practices of mourning. The repetitive playing of video games as an act of remembrance in mourning is a relatively novel iteration of grief. On the other hand, the ancient practice of pilgrimage could be compared to entry into virtual places of play. Such virtual places become separate yet integrated spheres of existence within the lived experiences of everyday life. Death, dying and mourning exist within the mechanics and narratives of contemporary video games; however, what is explored is the potential of video games to become sites where bereavement is recognised, incorporated and expressed – new experiences of bereavement which may manifest in contemporary artworks. Secondly, the melancholy object, as articulated by Margaret Gibson (2004: 289), is a central component of this study. The melancholy object signifies memory, which is inherent to the mourning process and, as such, could be described as the memorialised object of grief (Gibson, 2004: 289). I propose that, along with other everyday objects that can be recognised as melancholy objects, technological devices, such as cell phones, computers or video game consoles could be considered on some occasions as melancholy devices that have the potential to digitally recall the deceased through images, photographs, videos and social media sites. Lastly, I argue that diverse sites of grief, including everyday sites – such as cemeteries, grassroots memorials or roadside shrines – become imaginatively intertwined with virtual or digital sites – such as online sites to grieve, commemorative social media sites, videos, digital photographs or the virtual places of video games. This occurs when the bereaved person engages with images and art about grief and loss. Sites where grieving and commemoration take place provide valuable insight into the meaning attached to the sites of death by the bereaved throughout history. My hypothesis is that different types of sites have the innate ability to overlap with one another. This ability of everyday, virtual and digital sites to influence and overlap one another in contemporary society is explored visually. Furthermore, these sites are considered in terms of their potential to reveal other sites of memory within the body of the bereaved when memorialisation occurs. I conclude that all these attributes of grief and commemoration are intimately connected to the body of the bereaved, which becomes the moving and living site where memorialisation in inner pictures takes place. Such inner pictures are closely connected to - sometimes as the catalysts of - artistic exploration.
Dissertation (M.A. (Fine Arts))--University of the Free State, 2020
Keywords: Death; Mourning; Loss; Grief; Images; Pictures; Photograph; Place; Avatar; Sites; Video games; Melancholy object; Digital; Virtual; Drawing; Digital drawing